The rise of cities in north-west Europe - Verhulst, Adriaan E. (Themes in international urban history., 1999)
Examines fifteen towns, mainly situated on the rivers Meuse and Scheldt and along the North Sea coast of present-day Belgium, Holland and France. The author provides details of the impact of political, military, ecclesiastical, economic and social factors on the development of these towns.